2013
DOI: 10.2105/ajph.2013.301628
|View full text |Cite
|
Sign up to set email alerts
|

Housing First Improves Residential Stability in Homeless Adults With Concurrent Substance Dependence and Mental Disorders

Abstract: People with mental disorders might achieve similar levels of housing stability from Housing First regardless of whether they experience concurrent substance dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 48 publications
5
53
0
1
Order By: Relevance
“…Crucially, large gains in the time spent in housing were generally achieved and maintained over 2 years regardless of SUD status at baseline. This finding is consistent with the study by Rosenheck et al and builds upon prior analyses from the AHCS trial . Nonetheless, results from our study indicated that people with SUD in both the HF and usual care groups spent slightly less time in stable housing than did people without SUD, and they were somewhat less likely to be housed at study end (see Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Crucially, large gains in the time spent in housing were generally achieved and maintained over 2 years regardless of SUD status at baseline. This finding is consistent with the study by Rosenheck et al and builds upon prior analyses from the AHCS trial . Nonetheless, results from our study indicated that people with SUD in both the HF and usual care groups spent slightly less time in stable housing than did people without SUD, and they were somewhat less likely to be housed at study end (see Fig.…”
Section: Discussionsupporting
confidence: 93%
“…SUD is one such variable, given its high prevalence in this population, its impact on outcomes and questions related to the effectiveness of HF in this subgroup. Preliminary analyses from one AHCS study site found no difference in housing stability at 1 year by either frequency of substance use or SUD ; nor did substance‐related problems emerge as a predictor of housing instability in an analysis focused on identifying the factors that characterized HF participants who continued to experience unstable housing after their first year in the AHCS study . However, no analysis to date has tested whether SUD moderates the effectiveness of HF in the full national sample.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it does not follow the original scatter-site version of the housing-first philosophy. 19 Early studies of housing-first approaches have shown that they improve housing stability, 20,21 decrease criminal activity and jail bookings, [22][23][24] improve recovery trajectories for those struggling with mental illness, 25 and even help reduce substance use. [26][27][28] One study also found a potential reduction in acute care medical costs associated with housing first practices.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with co-occurring mental illness and substance use problems are another subpopulation for whom there are unique challenges in service provision. Although housing outcomes using best-practices are positive for this group (e.g., Palepu, Patterson, Moniruzzaman, Frankish, & Somers, 2013), service providers may have to manage safety concerns and sudden behaviours (e.g., associations with drug dealers, disappearances following relapse); longer trajectories toward housing stability, trust of providers, and recovery; and locating substance use treatment services in resource-poor communities (Foster, LeFauve, Kresky-Wolff, & Rickards, 2010). The additional challenges that service providers face in working with groups that have more complex needs require greater attention.…”
Section: Serving Complex Needsmentioning
confidence: 99%